2002
DOI: 10.1002/app.10424
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of water‐soluble chitosan derivatives and their antibacterial activity

Abstract: Carboxymethyl chitosan sodium (CMCTS) was synthesized by chitosan and chloroacetic acid under an alkali catalyst. Acrylic acid sodium salt and methylacrylic acid sodium salt were grafted onto CMCTS to obtain copolymers with good water solubility. The graft reaction was carried out at 70°C for 2 h, and ammonium persulfate was used as an initiator. The structure changes of chitosan and its derivatives were investigated by the FTIR. The antibacterial activity of chitosan derivatives against Staphylococcus aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 156 publications
2
17
0
1
Order By: Relevance
“…Liu et al [34] reported that the antibacterial activity of CS oligomers seems to be caused mainly by the inhibition of the transcription from DNA. The cationic amino group of CS can associate with anions on the bacteria wall, suppress its biosynthesis, disrupt the mass transport across the wall, and accelerate the death of the bacteria [35]. Because the amino density of CS in PAN-C-H membrane was lower than PAN-C due to the immobilization of HEP, the antibacterial activity was lower than that of PAN-C membrane.…”
Section: Permeabilitymentioning
confidence: 99%
“…Liu et al [34] reported that the antibacterial activity of CS oligomers seems to be caused mainly by the inhibition of the transcription from DNA. The cationic amino group of CS can associate with anions on the bacteria wall, suppress its biosynthesis, disrupt the mass transport across the wall, and accelerate the death of the bacteria [35]. Because the amino density of CS in PAN-C-H membrane was lower than PAN-C due to the immobilization of HEP, the antibacterial activity was lower than that of PAN-C membrane.…”
Section: Permeabilitymentioning
confidence: 99%
“…Recently, various kinds of chemical modification of chitosan, such as akylation reaction [11], quaternary reaction [12], carboxymethyl reaction [13], ring-opening reaction [14] and acylate reaction [15,16] to provide water-soluble or organic-soluble productions are of prime interest to generate novel biomaterials, Many research reported on the chitosan derivative applications in the fields of biomaterials such as soft tissue reconstruction [17], cartilage tissue engineering in recent years [18], cartilage regeneration [19], and drug release [20]. But the procedure of the methods was complex, the cost was high, and toxic segment was introduced during the process which changes the properties of the chitosan derivative at all.…”
Section: Introductionmentioning
confidence: 99%
“…CMCs was prepared by a modified method to that adapted from Xie et al 34 The intrinsic viscosity of the prepared CMCs in 0.1M aqueous NaCl at 30 C is $ 5.1 dL/g. The structural changes of Cs and its derivatives (CMCs and CMCs-g-MAA) were confirmed by FTIR (Fig.…”
Section: Preparation Of Cmcs and Cmcs-g-maa Copolymermentioning
confidence: 99%
“…Water-soluble CMCs was prepared by a modified method to that described by Xie et al 34 In a typical procedure, 2 g of Cs were put in 500 mL reactor and suspended in 60 mL of isopropyl alcohol at room temperature for 5 h. To the swollen Cs suspension, 75 mL of aqueous NaOH solution (60% w/v) were added and then the whole mixture was refluxed at 85 C for 2 h. Then, 100 mL of aqueous monochloroacetic acid solution (60% w/v) were added over a period of 15 min. The mixture was heated with stirring, at 65 C for further 4 h. The reaction mixture was then neutralized using HCl solution (5M).…”
Section: Preparation Of Cmcsmentioning
confidence: 99%
See 1 more Smart Citation